2007
DOI: 10.1111/j.1365-2230.2006.02322.x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of azithromycin on reactive oxygen species in rosacea

Abstract: Rosacea patients have higher ROS levels than healthy controls. The results of our study support the antioxidant properties of azithromycin in rosacea.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
60
0
10

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(72 citation statements)
references
References 23 publications
2
60
0
10
Order By: Relevance
“…In rosacea lesions, there was a higher ROS activity and a lower SOD level when compared to the controls [6]. The inhibition of ROS activity in neutrophils with various topical and systemic drugs used in the treatment of rosacea supports the "oxidative stress phenomenon" hypothesis [7][8][9]. On the other hand, PON1 is an enzyme having antioxidant and anti-inflammatory activity and it was found that serum PON1 levels decreased in rosacea [10].…”
Section: Introductionmentioning
confidence: 65%
“…In rosacea lesions, there was a higher ROS activity and a lower SOD level when compared to the controls [6]. The inhibition of ROS activity in neutrophils with various topical and systemic drugs used in the treatment of rosacea supports the "oxidative stress phenomenon" hypothesis [7][8][9]. On the other hand, PON1 is an enzyme having antioxidant and anti-inflammatory activity and it was found that serum PON1 levels decreased in rosacea [10].…”
Section: Introductionmentioning
confidence: 65%
“…24 The best results of azithromycin are achieved at the end of 4 weeks and maintained until 12 weeks. 64 For prolonged effect, the drug may be used for several months in reduced dosages. A study comparing oral azithromycin with doxycycline for 3 months found both drugs to be equally efficacious, but the azithromycin group had more patients with diarrhea, while the doxycycline group had some patients who experienced epigastric pain.…”
Section: Azithromycinmentioning
confidence: 99%
“…Reaktywne formy tlenu (ROS), takie jak aniony nadtlenkowe, rodniki hydroksylowe, tlen cząstecz-kowy i nadtlenek wodoru, powstają jako efekt wydzielania przez granulocyty wielojądrzaste, jak rów-nież w wyniku działania promieni słonecznych, co prowadzi do uszkodzenia tkanek [17,18].…”
Section: Rola Reaktywnych Form Tlenuunclassified
“…Z tego względu podejmowane są ciągle próby stosowania innych leków z tej grupy. Szczególne zainteresowanie wzbudza azytromycyna, która istotnie hamuje powstawanie ROS, ponadto wydaje się hamować produkcję cytokin prozapalnych [17,75] i w szeregu doniesień dotyczących pojedynczych pacjentów lub niewielkich grup chorych okazała się bardzo skuteczna w rosacea [79]. Dotychczas nie ma ustalonego schematu podawania tego leku.…”
unclassified